'AR11LE24', a Soft Red Winter Wheat Adapted to the Mid‐South Region of the USA. Issue 3 (3rd May 2018) - Mason, R. E.; Johnson, J. W.; Mergoum, M.; Miller, R. G.; Moon, D. E.; Carlin, J. F.; Harrison, S. A.; Babar, M. A.; Murphy, P.; Ibrahim, A. M. H.; Sutton, R.; Blount, A. R.
Abstract : 'AR11LE24' (Reg. No. CV‐1142, PI 678970) is a soft red winter wheat ( Triticum aestivum L.) co‐developed by the University of Arkansas's Division of Agriculture and the University of Georgia and released in 2015 under the Southeastern University Grains (SunGrains) cooperative. AG South Genetics licensed AR11LE24 as 'AGS 2055' in 2016. AR11LE24 is a selection from the cross of two Georgia breeding lines (GA961591‐3E42 and GA96229‐3A41). The F1 plants were grown in the field in Plains, GA. The pedigree method of breeding was used to advance individual spike selections from the F2 to F5 generations to reach an adequate level of homozygosity. Subsequent generations of AR11LE24 were evaluated in Arkansas and in regional performance nurseries and official state trials from 2010 to 2015. AR11LE24 has shown excellent adaptation and strong performance in Arkansas, Texas, and the region, where it consistently outyielded commercially available wheat cultivars. From 2013 to 2015, AR11LE24 had a 2‐yr statewide mean yield in the Arkansas Wheat Cultivar Performance Test of 5246 kg ha −1 . In the 2013–2014 Texas Uniform Variety Trial for soft wheat, AR11LE24 had a statewide yield of 5535 kg ha −1 . It is resistant to stripe rust, leaf rust, and local races of stem rust and contains SBM1 for Soil‐borne wheat mosaic virus resistance. It also shows moderate resistance to other economically important diseases and pests in the southeastern region of the United States.